Cultura Chinchorro : las momias artificiales más antiguas del mundo - Arriaza, Bernardo T. (Imagen de Chile, 2015)
"Comprehensive study of 282 examples permits classification, description, and interpretation of mummification techniques and of details of health, diet, technology, settlement, and society between 5000 and 1700 BC. Argues that mummification was invented in Arica-Camerones region to insure continuity of life in the context of environmental uncertainty"--Handbook of Latin American Studies, v. 57.